Đáp án + Giải thích các bước giải:
a) Dựa vào đề bài, xác định : a^{3}=(1)/(8)x^{3}->a=(1)/(2)x và b^{3}=27y^{3}->b=3y
->((1)/(2)x-3y)^{3}=(1)/(8)x^{3}-3.((1)/(2)x)^{2}.3y+3.(1)/(2)x.(3y)^{2}-27y^{3}
=(1)/(8)x^{3}-(9)/(4)x^{2}y+(27)/(2)xy^{2}-27y^{3}
b) Dựa vào đề bài, xác định : 2ab=(1)/(4)x và b^{2}=1
->b=1 và a=(1)/(8)x
->((1)/(8)x-1)^{2}=((1)/(8)x)^{2}-(1)/(4)x+1
=(1)/(64)x^{2}-(1)/(4)x+1
c) Dựa vào đề bài, xác định : a^{3}=y^{3}->a=y và b=3x
->(y+3x)^{3}=y^{3}+3.y^{2}.3x+3.y.(3x)^{2}+(3x)^{3}
=y^{3}+9xy^{2}+27x^{2}y+27x^{3}
d) Dựa vào đề bài, xác định : a=2x,b=3y
->(2x-3y)(2x+3y)=(2x)^{2}-(3y)^{2}